The Influence of Fintech , Financial Literacy and Financial Inclusion on the Sustainability of MSMEs in Makassar City - Andi Lutfyatul Fadillah; Linda Arisanty Razak (www.amertainstitute.com, 2024)
This study aims to explore the impact of Financial Technology ( Fintech), financial literacy, and financial inclusion on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Makassar City. In an increasingly digital era, the adoption of Fintech is expected to increase the ease and efficiency of operations for MSME actors. Meanwhile, a high level of financial literacy allows business owners to manage their finances more effectively, and financial inclusion plays an important role in expanding access to financial services. This study uses a quantitative approach with multiple linear regression analysis to explore the relationship between these variables . The findings of this study indicate that the use of Financial Technology ( Fintech ), financial literacy, and access to financial inclusion have a positive impact on the sustainability of MSMEs in Makassar City